2003
DOI: 10.1172/jci200317246
|View full text |Cite
|
Sign up to set email alerts
|

A functional androgen receptor is not sufficient to allow estradiol to protect bone after gonadectomy in estradiol receptor–deficient mice

Abstract: Although the role of estradiol in maintaining bone mass is well established, the relative contributions of the estradiol receptors ERα and ERβ and of the androgen receptor (AR) remain controversial. To determine the role of ERα-mediated, ERβ-mediated, and non–ER-mediated mechanisms in maintaining bone mass, gonadectomy and estradiol treatment were studied in ER-knockout mice. Estradiol treatment of ovariectomized ERαβ–/– mice failed to prevent bone loss, precluding significant effects of estradiol on bone thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(75 citation statements)
references
References 29 publications
6
67
0
2
Order By: Relevance
“…In the female skeleton, ERαβ KO decreased bone mass, confirming that both ER subtypes function to maintain bone mass [22].…”
Section: Deletion Of Erα and βmentioning
confidence: 70%
“…In the female skeleton, ERαβ KO decreased bone mass, confirming that both ER subtypes function to maintain bone mass [22].…”
Section: Deletion Of Erα and βmentioning
confidence: 70%
“…Finally, the similarity of melting point of ProStrakan estren (210°C) to that of Steraloid estren (206-207°C, according to the manufacturer) indicated that the crystalline structure of both compounds is the same. Anti-estrogen (PSK3668) and anti-androgen (RU58642) were administered at 10 mg/kg/d and 30 mg/kg/d, respectively, by daily subcutaneous injection, as previously described (27). In the dose-response experiments, WT male C57BL/6 mice were subjected to ORX and treated with slow-release pellets delivering estren-α (Steraloids, 7.0; 1.8 or 0.9 mg/mouse/35 days), DHT (Steraloids; 3.5 mg/mouse/35 days), or vehicle.…”
Section: Figurementioning
confidence: 99%
“…Peripheral quantitative CT. Densitometry was performed with the Stratec peripheral quantitative CT (pQCT) XCT Research SA + (software version 5.4B; Norland Medical Systems Inc.) operating at a resolution of 70 μm as previously described (27). Briefly, metaphyseal pQCT scans of dissected right tibiae were performed to measure trabecular bone mineral density.…”
Section: Figurementioning
confidence: 99%
“…Because of this possible dual mode of action of androgens, the contribution of androgens and estrogens in the regulation of the male skeleton remains complex. All three sex steroid receptors are expressed in bone cells [4], and experimental animal studies have shown that each of these three receptors mediates site-specific skeletal effects of sex steroids [5][6][7][8][9][10][11][12]. In addition, recent in vitro studies suggested that the membrane G proteincoupled receptor GPR30 might also be a potential estrogen receptor ( Fig.…”
Section: Introductionmentioning
confidence: 99%